A literature review on peers' ICT support, teachers' ICT support and family involvement on students' engagement in ICTs for learning mathematics among Iranian secondary school students - Kaboodvand, Tahereh; Mohd Ayub, Ahmad Fauzi; Md. Yunus, Aida Suraya; Mahmud, Rosnaini (Human Resource Management Academic Research Society, 2017)
This paper is an attempt to propose a framework for elucidating the effects of Information Communication Technology (ICT) in enabling high-school math students' capacity and facilitating students' learning desire and involvement. The paper also argues that students' engagement with ICT is boosted as a result of the ICT utilization and entails their teachers' sustenance, peers' influence, and family support. In other words, it is argued that getting engaged with ICT plays an instrumental role to stimulate teachers and peers support along with family involvement. Namely, a triangle is formed that contributes to the learning desire towards ICT engagement for approaching math. To this goal, the paper empirically demonstrates that the application of ICT among Iranian secondary mathematics students has resulted in positive output. For measuring the independent variables such as school leadership, teachers’ higher productivity, peers’ ICT support and family involvement under ICT introduction and presentation in mathematics classrooms, this study utilizes the data collected from the respondents regarding their opinions about the effect of ICT engagement in learning Mathematics. The study will also play an essential role in linking the gap that exists in ICT research between Iranian education center and the rest of the world.